Work Environment and Work Stress - Edwin Karim (Cattleya Darmaya Fortuna, 2025)
The purpose of this study was to determine how much influence the work environment has on the work stress of netting employees at PT Indoneptune Manufacturing. This research uses an associative quantitative approach by conducting a survey to the field. The population in this study were employees who worked at PT Indoneptune Manufacturing. Work environment affects work stress. That respondents are responding to the current working environment in the company to create a more comfortable working environment.. The research uses the production section as the research sample. This study uses production employees as a sample to examine the effect of work environment on work stress. The researcher found that employees often leave due to illness, which is an indicator of work stress.